1990
DOI: 10.1111/j.1744-7348.1990.tb06608.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cypermethrin on the feeding of mustard beetles Phaedon cochleariae (F.)

Abstract: Cypermethrin deposits on sprayed (3, 6, 9, 12 and 15 g ha-') radish leaves caused a significant antifeedant effect on third instar larvae and adults of mustard beetles.There was a significant inverse relationship between feeding and dose for both stages. In the case of adults on deposits of 1, 3 and 6 g ha-', feeding was reduced by 60-75% but no mortality was recorded. Much less uniform feeding was associated with higher application rates (9, 12 and 15 g ha-I) with low mortality at the two highest doses. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…Some degree of fungicide repellancy has been demonstrated for eight of the ten fungicides tested (five significantly so). Similar observations of an antifeedant effect has been observed in P. cochleariue fed on leaves treated with a pyrethroid insecticide (HAJJAR and FORD 1990). Lack of differences in the mean size of the feeding hole suggested that once the repellency had been overcome, normal feeding behaviour commenced.…”
Section: Fungicide Repellencysupporting
confidence: 76%
See 1 more Smart Citation
“…Some degree of fungicide repellancy has been demonstrated for eight of the ten fungicides tested (five significantly so). Similar observations of an antifeedant effect has been observed in P. cochleariue fed on leaves treated with a pyrethroid insecticide (HAJJAR and FORD 1990). Lack of differences in the mean size of the feeding hole suggested that once the repellency had been overcome, normal feeding behaviour commenced.…”
Section: Fungicide Repellencysupporting
confidence: 76%
“…Previous workers have detected sub-lethal effects of insecticides on beneficial insects in field crops. These have been expressed as reduced feeding (DEMPSTER 1968;HAJJAR and FORD 1990) and increased foraging movements (CHIVERTON 1984); sub-lethal effects of fungicides have been demonstrated only in the laboratory (IRVING and WYATT 1973;SELL 1985) and in glasshouses (HASSAN 1974;ELENKOV et al 1984;THACKER and HICKMAN 1991).…”
Section: Fungicide Repellencymentioning
confidence: 99%
“…Coats et al, 1979;Tripathi et al, 1988;Wiles & Jepson, 1992) and in the field (eg. Such sub-lethal effects are well documented for the pyrethroid insecticides and examples include the repellent/irritant responses shown by aphids (Highwood, 1979;Rice et al, 1983;Lowery & Boiteau, 1988;Adams & Hall, 1990), mites (Iftner & Hall, 1983;Penman & Chapman, 1983;Berry et al, 1990) and honeybees (Delabie et al, 1985) and also antifeedant responses shown by Lepidoptera (Tan, 1981(Tan, , 1982 and Coleoptera (Hajjar & Ford, 1990). Such sub-lethal effects are well documented for the pyrethroid insecticides and examples include the repellent/irritant responses shown by aphids (Highwood, 1979;Rice et al, 1983;Lowery & Boiteau, 1988;Adams & Hall, 1990), mites (Iftner & Hall, 1983;Penman & Chapman, 1983;Berry et al, 1990) and honeybees (Delabie et al, 1985) and also antifeedant responses shown by Lepidoptera (Tan, 1981(Tan, , 1982 and Coleoptera (Hajjar & Ford, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Vickerman et al, 1987;Poehling, 1988; Zoebe]ein, 1988; Wiles, 1992) but few have looked at the more subtle, sub-lethal influence that contact with pesticide residues may have upon their behaviour. Such sub-lethal effects are well documented for the pyrethroid insecticides and examples include the repellent/irritant responses shown by aphids (Highwood, 1979;Rice et al, 1983;Lowery & Boiteau, 1988;Adams & Hall, 1990), mites (Iftner & Hall, 1983;Penman & Chapman, 1983;Berry et al, 1990) and honeybees (Delabie et al, 1985) and also antifeedant responses shown by Lepidoptera (Tan, 1981(Tan, , 1982 and Coleoptera (Hajjar & Ford, 1990). Relatively little information is available however, concerning the possible sub-lethal effects of pyrethroids on predators in the field.…”
Section: Introductionmentioning
confidence: 99%
“…This result may be attributable to a repellent effect of the cypermethrin (Wood et al ., ). Although the anti‐feeding effect produced by pyrethroids has not been demonstrated in T. infestans , exposure to cypermethrin has been shown to decrease food intake in other insects, such as larvae of Pieris brassicae (Lepidoptera: Pieridae) (Tan, ) and the beetle Phaedon cochleariae (Coleoptera: Chrysomelidae) (Hajjar & Ford, ). In T. infestans , this ‘repellence effect’ decreases with the washing out of the insecticide, but does not disappear completely until 45 days after application (Amelotti et al ., ; Amelotti, ), and its effect on the ingestion of blood is one of the key factors regulating the population density of T. infestans (Gorla & Schofield, ).…”
Section: Discussionmentioning
confidence: 99%